Cardoon (Cynara cardunculus L.): different multipurpose food industry applications - Barbosa, Cássia (2022)
Cynara cardunculus L. (Asteraceae) is a multipurpose crop native to the Mediterranean area, commonly called cardoon. It comprises three botanical varieties: the globe artichoke (var. scolymus (L.) Fiori), the cultivated cardoon (var. altilis DC.), and the wild cardoon (var. sylvestris (Lamk) Fiori). Cardoon can develop in adverse climate conditions, low inputs, high temperature, severe drought, and infertile soils as a resistant species. Yet, it can persist for several years, re-sprouting annually. Cardoon can be used for different purposes due to its composition. For instance, the fleshy stems and the immature heads are used in Mediterranean cuisine. The flowers are used in the production of some cheeses as vegetal rennet. In traditional medicine cardoon is used due to its high content in cynarin and silymarin. Kidneys and liver malfunction, high blood cholesterol levels, diabetes, and cancer are some of the medicinal applications. On the other hand, cardoon’s by-products, leaves, stems and seeds, can be used to produce biomass for energy, biodiesel, seed oil, animal feed and paper pulp. Cardoon’s leaves bioactive properties (e.g.: antioxidant and antimicrobial activities) are due to its excellent polyphenol profile, rich in chlorogenic acid and flavonoids. As leaves represent, on average, about 60% of total cardoon waste, in the context of a circular economy it is essential to take advantage of its composition in bioactive compounds. Concerning the food industry, leaves, and leaves extracts bioactivity may represent an added value as a food additive, as an ingredient in developing a novel food, or in active food packaging to control lipid oxidation and microbial deterioration. Hence, this study aims to address the current food applications of cardoon’s leaves and their functional properties and explore new potential ones adding value to its properties.